Synthesis and characterization of zirconia-calcia nanocomposite for dental application - Ab Ghani, Nur Atikah (2022)
This study was designed to examine zirconia stabilized by nano calcium oxide (CSZ) synthesized using sol-gel method as for potential material for dental implant, dental crown and bridgework substructures. Some parameters such as medium of reaction, concentrations of organic additive, and concentration of precipitating agents were investigated. The optimum calcia-zirconia powder was selected and pressed in stainless steel mould using a hydraulic press under 5 tons (60 MPa) pressure. The pressed samples were sintered at different temperatures of 1200, 1300 and 1400 °C for 2 hours. The bioactivity study was carried out on the pressed samples sintered at 1400 °C to examine the ability of apatite formation on its surface in a simulated body fluid (SBF) solution for different periods within 4 weeks at 37.0 °C. In the presence of 2.0 M NH3 in ethanolic solution, calcia-zirconia powder was successfully obtained, where the particles were spherical in shape with less agglomeration, and consisting of a nanoscale dimension ranging from 40 to 80 nm with the highest BET surface area of 43.65 m2/g. The CSZ1400 pellet showed cubic phase zirconia with XRD analysis, and it gave the smoothest texture after polishing when viewed under FESEM images. Density measurement of CSZ1400 produced an optimum relative density value of 94.95±1.013 %. The values of Vickers microhardness of CSZ were increased with the increase in sintering temperatures ranging from 435.17±27.89 to 640.11±31.97 HV (4267±273.58 to 6277±313.44 MPa), where CSZ1400 was comparable with CEREC zirconia (p>0.05). The bioactivity test on CSZ1400 revealed the apatite layer formation on its surface which indicated the biocompatibility and potential bone forming ability. Physical, mechanical and biological study proved that CaO stabilized zirconia using sol-gel method may be used as an alternative to the current zirconia available in the market for dental application.